Systematic Literature Review: The Use of Technology-Based and Non Technology-Based Tennis Learning Aids in Hitting Motion Skills - Zakaria, Dhani Agusni; Silvy Juditya; Heryanto, Mamat; Nabila, De Alya Putri Dewi (Journal of Physical and Outdoor Education, 2025)
This study aims to identify the effectiveness of using tennis learning aids in improving tennis stroke skills at the beginner level. The research method used is a Systematic Literature Review with an Agile SLR approach through searching national and international scientific articles in the period 2019–2025. Of the 74 identified articles, 17 articles were deemed eligible for analysis. The results showed that 71% of the articles discussed the use of technology-based aids such as interactive multimedia, automatic ball throwing machines, artificial intelligence-based robots, and motion sensors, which have been proven to increase training efficiency, provide rapid feedback, and enrich learning innovation. Meanwhile, 29% of the articles emphasized non-technological aids in the form of simple equipment modifications such as low-compression balls, scaled rackets, and mini courts that effectively support basic training, reduce the risk of injury, and facilitate technique adaptation for beginners. The conclusion of this study confirms that there are two types of tennis learning aids at the beginner level to improve stroke skills: both technological and non-technological learning aids are considered effective in improving tennis stroke skills, especially at the beginner level. Therefore, integrating both is an ideal strategy to improve stroke skills for beginners..